Vehicle miles traveled and the built environment: New evidence from panel data - Keith Ihlanfeldt (Journal of Transport and Land Use)
There has been considerable interest in the impact that the built environment has on vehicle miles traveled (VMT). While this issue has been extensively researched, due to the heavy reliance on cross-sectional data, there remains uncertainty regarding how effective local land-use planning and regulation might be in reducing VMT. Based on a 13-year panel of Florida counties, models are estimated that relate VMT to new measures of the spatial distribution of alternative land uses within counties and county urban expansion. Identification of causal effects is established by including year and county fixed effects, along with an extensive set of control variables, and instrumenting those land uses that may be endogenous. Incremental annual changes in the spatial concentration of alternative land uses are found to affect VMT. The policy implication is that appropriate land-use policy can reduce VMT and should be considered part of the strategy for dealing with the problem of global warming.